2017
DOI: 10.1159/000477670
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Secondary Traumatization in Interpreters for Refugees: A Cross-Sectional Study

Abstract: Background: A substantial proportion of refugees, fleeing persecution, torture, and war, are estimated to suffer from psychological traumatization. After being sheltered in reception centers, the refugees come in close contact with different occupational groups, e.g., physicians, social workers, and interpreters. Previous studies ascertained that such interpreters themselves often suffer from primary psychological traumatization. Moreover, through translating refugees' potentially traumatic depictions, the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
80
3
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 58 publications
(105 citation statements)
references
References 53 publications
14
80
3
8
Order By: Relevance
“…This phenomenon is called secondary traumatization and can be identified in various helping professions including social workers and trauma therapists ( 16 18 ). In addition, Kindermann et al recently reported that 21% of interpreters working with refugees suffered from secondary traumatization ( 19 ). The general prevalence rates of secondary traumatization in caregivers illustrate the need for research on risk and resilience factors of secondary traumatization especially in professionals working with highly traumatized patients.…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is called secondary traumatization and can be identified in various helping professions including social workers and trauma therapists ( 16 18 ). In addition, Kindermann et al recently reported that 21% of interpreters working with refugees suffered from secondary traumatization ( 19 ). The general prevalence rates of secondary traumatization in caregivers illustrate the need for research on risk and resilience factors of secondary traumatization especially in professionals working with highly traumatized patients.…”
Section: Introductionmentioning
confidence: 99%
“…The discrepancy between the psychotherapists' high trauma load and the few concessions made by an emotional viewpoint contingent upon this would seem to be mere social expediency [18]. High avoidance levels seem to be evident, namely that they play down their mental stress; they are "professionals" and as such are immune to mental decompensation [34][35][36][37][38]. In the case of potential stigmatising topic areas such as psychological instability and social crisis situations, there is an automatized reversal of roles into that of the expert; even barely sociallyacceptable coping strategies such as heavy smoking, alcohol or sexual debauchery have only been observed at a distance in other psychotherapists and are not confirmed from their own experience.…”
Section: Discussionmentioning
confidence: 99%
“…Diese Form hilft klarzustellen, dass der Dolmetscher kein Ansprechpartner ist und fördert so das Gelingen der Beziehung zwischen BehandlerIn und PatientIn [22]. Jedoch erhöht eine Verdolmetschung in der Ich-Form das Risiko einer sekundären Traumatisierung -sprich die Übertragung affektiver Symptomatik traumatisierter PatientInnen auf den Dolmetscher [23,24]. Eine Verdolmetschung in der dritten Person hingegen erleichtert eine Distanzierung von den vermittelten Inhalten, was insbesondere im Hinblick auf Berichte traumatischer Erfahrungen der PatientInnen von Bedeutung für DolmetscherInnen ist.…”
Section: Zufriedenheiten Der Dolmetscherinnen Und Behandlerinnenunclassified